CONFINED QUEST FOR CONTINUITY: THE CATEGORICAL VERSUS CONTINUOUS NATURE OF ATTACHMENT. Issue 3 (September 2014) - van IJzendoorn, Marinus H.; Bakermans‐Kranenburg, Marian J.
ABSTRACT The use of the Adult Attachment Interview (AAI) in the NICHD Study of Early Child Care and Youth Development (NICHD SECCYD) is a major contribution to the field. The core of the current monograph pertains to psychometrics (dimensional vs. categorical assessment) of the AAI and continuity of attachment over time. We argue that the generalizability of the conclusions with regard to the AAI is limited to similar groups, because of the low‐risk adolescence nature of the sample, with concomitant underrepresentation of the preoccupied and unresolved classifications in the current sample (each only 3%). Baron von Münchhausen's paradox emerges in the use of the same source of coded data for categorical classifications and continuous scales of the AAI scoring procedure. At the same time, the monograph convincingly demonstrates that earned security cannot be assessed retrospectively in a valid and reliable manner, and the study highlights the power of scientific collaboration as realized in the NICHD SECCYD.